Does state border matter in internal migration in India? - Pradhan, Kanhu Charan (H. : ĐHKT, 2020)
Migration is crucial for the economic growth of an economy through efficient allocation of labour resources. At the same time, it acts as a major tool for eradicating poverty and improving the standard of living of people. All the major economies in the world are characterized by a high migration rate. On the contrary, Indians are known to be less mobile, even in comparison to other developing countries of the same region (UN 2013). According to the 2011 census, 37% of the total Indians have migrated during their lifetime. Further, the migration rate is much lower for the male population (23%) than the female population (53%).